Multiphasic Computed Tomography Enhancement Characteristics and Utility of Delayed Phase in Infiltrative Hepatocellular Carcinoma - Singh, Tarvinder; Mehta, Nandita; Gupta, Pankaj; Gulati, Ajay; Gulati, Mudita; Kalra, Naveen; Premkumar, Madhumita; Taneja, Sunil; Jearth, Vaneet; Sharma, Vishal; Duseja, Ajay (Indian Journal of Radiology and Imaging, 2024)
Objective The aims of this study are to compare the multiphasic contrast-enhanced computed tomography (CECT) characteristics of infiltrative hepatocellular carcinoma (HCC) with nodular HCC and to assess the conspicuity of infiltrative HCC on different phases of CECT.Materials and Methods This retrospective study comprised consecutive treatment-naive cirrhotic patients diagnosed with infiltrative and nodular HCC between January 2020 and December 2021 based on a multiphasic CECT (comprising arterial, portal venous, and delayed phases). The diagnosis of HCC was based on the Liver Imaging Reporting and Data System (LI-RADS) v2018 criteria (LR-4 and LR-5 lesions). Infiltrative HCCs are characterized by large, irregular, permeative lesions spread over multiple liver segments or lobes. Nodular HCCs comprise well-defined tumor nodules. Two radiologists independently reviewed all CT images. Additionally, lesion conspicuity on the arterial, portal venous, and delayed phases was assessed.Results One hundred fifty-eight patients (117 nodular and 41 infiltrative HCCs; mean age: 55.6 ± 17.2 years; 90 [56.9%] males) were included. Arterial phase hyperenhancement, portal venous/delayed phase washout, and delayed phase enhancing capsule were significantly associated with nodular HCCs (p = 0.002, 0.0001, and <0.0001, respectively). Portal vein, hepatic vein thrombosis, biliary dilatation, and ascites were significantly associated with infiltrative HCCs (p < 0.0001, 0.004, <0.0001, and 0.003, respectively). The interobserver agreement for the conspicuity of infiltrative HCC was the highest for the delayed phase (weighted kappa = 0.611).Conclusion Infiltrative HCCs show the major LI-RADS features less frequently compared with nodular HCCs, and venous thrombosis is an important clue to the diagnosis. The delayed phase of multiphasic CECT is critical to identifying these lesions.
Keywords: CT; hepatocellular carcinoma; LI-RADS; portal vein thrombosis